Organic selenium and the exercising horse - Dunnett, Cath E; Dunnett, M (MTT, 2008)
In horses, adequate dietary selenium (Se) is essential to support a range of selenoproteins and seleno-dependent enzymes including glutathione peroxidase (GPx) and thioredoxin reductase, which are vital for optimum functioning of the antioxidant, immune and reproductive systems. The natural abundance of Se in pastures, grains and forages displays marked geographical variation, but mostly only low levels of Se are present. Consequently, dietary supplementation is essential for horses and commonly implemented at the point of (feed) manufacture. Historically, inorganic Se sources, such as selenite, have been used, but margin of safety is narrow and efficacy has been questioned. More recently, replacement with organic Se sources, such as Se-enriched yeasts (containing selenomethionine and selenocysteine) has been advocated. A growing body of research suggests that organic Se sources enhance Se incorporation into tissues both at rest and during exercise and increases Se status, enzyme activities, antioxidant capacity and immune function in mature horses and foals. Organic Se appears to cause a greater relative increase in plasma Se over 28 d compared with selenite, although comparative effects were similar over 56 d for skeletal muscle Se and GPx and plasma GPx. Organic Se also produced a greater numerical but statistically insignificant increase in blood GPx activity than selenite during supplementation to horses over 112 d. Post-supplementation decline in blood GPx activity was also reduced in horses receiving organic Se. Other studies have indicated that pre- and post-partum organic Se supplementation in mares confers subsequent benefits in the foal through improved Se status.
Keywords: Ko; horse; organic and inorganic selenium; status; exercise; supplementation